South Asia Economic Focus, June 2011 : Food Inflation - World Bank (Washington, DC, 2013)
This report focuses on the impact of policies and exogenous shocks on food inflation. It deals with four elements: 1) the pass-through of global food (and other commodity) prices, 2) macroeconomic policies, 3) market regulation and short-term supply shocks, and 4) long-term structural shifts and the terms of trade between agriculture and other sectors of the economy. This report examines food and overall inflation trends in South Asia, which is experiencing relatively high inflation, and is home to a large number of poor. There are many more poor people who are net buyers of food than there are those who benefit from higher prices of agricultural products even in the predominantly rural countries of South Asia. The report examines both short-term and longer-term drivers of rising food prices in the region, including developments in international commodity prices, domestic supply shocks, accommodative demand side policies, structural changes in demand patterns, and long-term agricultural productivity trends. The impact on poverty is examined, as is the region's preparedness for food price shocks. The priorities laid out in the Bank's post-crisis directions paper (2010) and the mandates given to the Bank by the G20 are to focus on food price volatility, agriculture and food security, and agricultural productivity. In line with these priorities, the report ends with some policy directions to manage the macroeconomic impact of food price inflation, and the potential spillover into generalized inflation, to manage the social impact of the food price hikes, and to hedge against risks associated with food price volatility. The report is organized as follows: section two discusses the anatomy and short- and longer-run drivers of food and overall inflation in South Asia. Section three discusses the impact of government policies affecting agricultural marketing, inputs and trade in South Asian countries. Section four presents an assessment of the impact of food price increases on poverty and an assessment of the preparedness of South Asian countries social protection schemes to cope with this impact. Section five concludes with some policy directions that could be pursued by South Asia to improve agricultural productivity and mitigate the impact of food price volatility on its population.